PERDAGANGAN BESI PADA MASYARAKAT BIAK NUMFOR - Sonya M. Kawer (BALAI ARKEOLOGI PAPUA, 2010)
A commerce is a transaction activity done by the seller and buyer. The Biaknese has recognized the trade system long before the European came to Papua. The trade system known by the Biaknese is barter. The result of the contact between the Biaknese and the people outside the village like Tidore and Ternate produce the things like iron, beads, ceramics, fabrics, and pottery. The product that the Biaknese need is iron because iron can be made into spear, axe, machete, bracelet, etc.